Risk of Parkinson’s disease in patients with schizophrenia: Impact of antipsychotic medication use - Jin Yeon Gil; Kyung Hyun Min; Jun Hyeob Kim; Jun Hyuk Park; Ji Min Han; Kyung Eun Lee (PLoS ONE, 2026)
Background/objectives Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by motor and non-motor symptoms, and its incidence is steadily increasing. Schizophrenia (SCZ) is a severe psychiatric disorder involving both positive and negative symptoms. Both diseases share dopaminergic dysregulation, but the relationship between schizophrenia and PD and the role of antipsychotic treatment in the risk of PD are not well understood. This study aimed to explore the risk of PD in individuals with schizophrenia and assess the influence of antipsychotic medications on this risk. Methods This retrospective cohort study used a customized database from the National Health Insurance Service (NHIS) of South Korea, which included patients diagnosed with schizophrenia and matched controls. We performed propensity score matching and adjusted for various demographic, clinical, and comorbidity variables. Competing risk analysis and Cox regression were used to analyze the relationship between schizophrenia and PD, considering both antipsychotic medication exposure and comorbid conditions. Results We found that individuals with schizophrenia had a significantly higher risk of developing PD than the control subjects, with an adjusted hazard ratio of 3.198. Among schizophrenia patients, compared with control, risperidone use was associated with an increased risk of PD, whereas quetiapine use was associated with a reduced risk. Significant comorbidities, such as head injury and cerebrovascular disease, also contributed to the increased risk of PD. Conclusions Our study highlights the elevated risk of PD in individuals with schizophrenia, emphasizing the need for close monitoring of this patient population. The impact of antipsychotic medications, particularly risperidone and quetiapine, on the development of PD warrants further investigation to better understand the long-term effects of these treatments.